(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article delves into the grammatical features of adjectives and explores their role as words expressing the quality of a substance. Adjectives, as a fundamental part of language, play a crucial role in providing descriptive details and enhancing communication. This study specifically focuses on two primary categories of adjectives: qualitative and relative adjectives.